As vozes dos estudantes autazenses (noturno) em uma escola de EJA no enfrentamento dos desafios de permanência - Medeiros, Camila Campos (Brasil, 2025)
The research analyzes the challenges of accessing and remaining in school for young people and adults, in the EJA modality. We start from the following guiding questions: what factors influence the retention of young people and adults in Autazes schools? What are the main difficulties faced by young people at school? The present study had the general objective: to analyze the challenges of permanence for young people from EJA in High School in a Public School in the Municipality of Autazes-AM. To this end, the following specific objectives were established: carry out surveys on the historical context of Youth and Adult Education in the municipality of Autazes; identify the factors that influence the retention of young people and adults in Autazes schools; delimit the main difficulties faced by young people at school. The methodology used consisted of exploratory field research with a qualitative approach. The main authors used in this work were: Nunes and Feitoza (2008); Miranda (2012); Costa and Machado (2017), among others. It was identified through the results obtained that the EJA education modality still has challenges related to getting to school, intra-school and intra-family challenges faced on a daily basis. It is therefore concluded that there is a need to develop permanence policies that meet the needs of EJA students.